2002
DOI: 10.1021/jp026606m
|View full text |Cite
|
Sign up to set email alerts
|

Oil Chain-Length Effect on Wetting Transitions in Ternary Water + Oil + Surfactant Mixtures

Abstract: In the three-liquid-phase coexisting region of the system water + tetradecane + diethylene glycol monohexyl ether (C 6 E 2 ), the middle surfactant-rich phase undergoes a sequence of wetting transitions comprising nonwetting f partial wetting f complete wetting at the interface of oil-rich and water-rich phases as the temperature is raised from its lower critical consolute temperature toward its upper critical consolute temperature (J. Chem. Phys. 1993, 98, 4830). In this study, the effect of oil chain length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
1
24
1
Order By: Relevance
“…3) and boiling. All the studies reported in the literature with C i E j /n-alkane/water systems point out a similar linearity, even though on a narrower range of n-alkanes [59][60][61][62][63][64][65][66][67][68][69][70]. By contrast, both theoretical models based on the spontaneous curvature of the oil/water interface [71] or based on the partitioning of monomolecular surfactant monomers between oil and water [11] predict that T * should vary linearly with 1/ACN.…”
Section: Evolution Of the X-point Temperature With Increasing Acn Of mentioning
confidence: 85%
See 1 more Smart Citation
“…3) and boiling. All the studies reported in the literature with C i E j /n-alkane/water systems point out a similar linearity, even though on a narrower range of n-alkanes [59][60][61][62][63][64][65][66][67][68][69][70]. By contrast, both theoretical models based on the spontaneous curvature of the oil/water interface [71] or based on the partitioning of monomolecular surfactant monomers between oil and water [11] predict that T * should vary linearly with 1/ACN.…”
Section: Evolution Of the X-point Temperature With Increasing Acn Of mentioning
confidence: 85%
“…The optimal formulation does not correspond exactly to the same HLD for equal masses of water and oil (black line) and equal volumes of water and oil (grey line). [59][60][61][62][63][64][65][66][67][68][69][70][71][72] with n-alkanes and several selected oils. Experimental T * s for C 10 E 4 and these oils are also included, as well as the melting points of n-alkanes.…”
Section: Choice Of the Best Conditions For The Determination Of Eacnsmentioning
confidence: 99%
“…(CH 3 ) 2 (CH 2 ) m N ? -(CH 3 ) 2 C 12 H 25-2Br -it has been found that the CMC value increases with 'm' to a maximum at 'm' equals four and then decreases [19]. A very large hydrophobic polyethylene group Scheme 4 Synthesis of bis-quaternary ammonium cationic bola geminis using acrylic-modified rosin, Wei et al [17] Review on chemically bonded geminis with cationic heads… penetrates into the interior of the micelle and thus is removed from contact with the aqueous phase, which is the probable reason for the decrement of CMC [20].…”
Section: Gemini Versus Conventional Surfactants: Differences In Fundamentioning
confidence: 97%
“…For an oil/water system, the interfacial tension is determined by the natures of the surfactant and oil, concentration, and other environmental factors, such as electrolyte, temperature, or additives [7][8][9][10]. In this paper, a series of surfactants, alkanediyl-a, x-bis(alkyldimethylammonium bromide), were prepared, referred to below as m-s-m, where m and s respectively stand for the carbon atom numbers in the alkyl chain and the spacer, and the interfacial tensions between these gemini surfactant solutions and oil have been investigated.…”
Section: Introductionmentioning
confidence: 99%